A novel spiral-filter press for tomato processing: process impact on phenolic compounds, carotenoids and ascorbic acid content. (November 2017) - Kips, Lies; De Paepe, Domien; Van Meulebroek, Lieven; Van Poucke, Christof; Larbat, Romain; Bernaert, Nathalie; Van Pamel, Els; De Loose, Marc; Raes, Katleen; Van Droogenbroeck, Bart
Abstract: Industrial processing of fruit and vegetables can have detrimental effects on health-promoting phytochemicals. Here, a novel pilot-scale process using an innovative spiral-filter press followed by a thermal treatment was evaluated for the production of tomato juice. Three-month storage of the resulting juice was also evaluated. The process impact of the different unit processes, with emphasis on the novel spiral-filter pressing, was investigated for the three major compound classes present in tomato (ascorbic acid, phenolic compounds and carotenoids). The spiral-filter press processing did not seem to cause degradation of ascorbic acid, phenolic compounds or carotenoids, which can be ascribed to the fast processing in a low-oxygen atmosphere. Maintaining the native constitution of tomato to a great extent, the spiral-filter press thus offers potential for processing tomatoes and other vegetables into juices, smoothies and purees. Highlights: Spiral-filter press processing conserves ascorbic acid, phenolics & carotenoids. Low-oxygen processing minimizes oxidation. Thermal treatment led to a decrease in carotenoids, but further research is necessary. 49% of the phenolics, present in mashed tomato are transferred in the juice. 90% of the carotenoids, present in mashed tomato are transferred in the juice.